Rural Socio-Economic Impact of Arms Proliferation on Crime in Katsina-Benue State - Obademi, Agnes Olufunke; Jonathan, Chagba; Onuh, Omale (International Journal of Law and Society, 2023)
The study investigated the rural socioeconomic impact of arms proliferation on criminality in Katsina-Ala local government, Benue state, Nigeria. Two research questions guided the study, and a cross-sectional survey research design will be used to examine arms proliferation and criminality in Benue State. Area of the Study Katsina-Ala Local Government, while the sample size for the study was 400, the research uses cluster and random sampling techniques to select the study population. By simple random sampling, the names of the ten (12) council wards were written on pieces of paper, wrapped, dropped into a container and shaken thoroughly. Five (6) council wards out of the original ten (12) wards were randomly selected. The data collected through the questionnaire were analysed using frequency counts and percentages. From the findings, it was concluded from the research findings that even though arms proliferation is caused by so many factors, profitability and utilisation of small arms have been singled out as the primary cause of the unrest in Katsina-Ala Local Government Area of Benue State.